HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PEMBERIAN ASI EKSLUSIF - Septia, Qori Armiza; Zalni, Rummy Islami; Halimah, Siti; Yanti, Noprika (Ensiklopedia of Journal, 2023)
Exclusive breastfeeding is exclusive breastfeeding for 6 months without being given other foods except vitamins, minerals and drugs in the form of ORS, drops and syrup. One of the factors causing breastfeeding mothers not to breastfeed exclusively for 6 months is the lack of knowledge and attitude of mothers towards exclusive breastfeeding. According to the World Health Organization (WHO) breastfeeding until the age of 6 months in the world is still very low at 41%, while the target to be achieved in 2030 is 70%. The purpose of this study was to find out whether there is an influence between knowledge and maternal attitudes towards exclusive breastfeeding. This research will be conducted in July-August 2023. This study used analytical research methods with a correlational type with a Cross Sectional design with a sample of 57 respondents. The results of the study obtained a p-value of 0.026 which is lower than 0.05, meaning that there is a relationship between the level of knowledge of mothers and exclusive breastfeeding. While the results of the significance test based on maternal attitudes obtained a p-value result of 0.012 which is lower than the significance standard of 0.05, meaning that there is a relationship between maternal attitudes and exclusive breastfeeding. The researcher's suggestion is expected to be used as learning material for respondents to increase the knowledge and attitude of breastfeeding mothers towards exclusive breastfeeding.